4.0 Leadership Skills in Hospitality Sector - Santos, Vasco (2019)
This paper intends to analyses leadership skills in the hospitality sector in the era of 4.0 industry. The purpose is to explore the role of multi‐level forms of leadership and the profiles identified by the hospitality professionals. This is a quantitative study based on an online survey applied to two hotels, and the following research question have guided the present study: What are the 4.0 Leadership Skills in the hospitality sector? To answer the research question, the main technique to collect data was a questionnaire allowing to investigate the main issues related to 4.0 leadership skills. The results of the research are the identification of the leadership skills profiles, being this research significant for managers and leaders when developing organizational interactions from a multi‐level efficacy perspective. The conceptual contribution of the paper is a fresh macro‐analytical perspective concerning 4.0 leadership skills in the hospitality sector.